MACRONONE, A NOVEL DIEPOXYLIGNAN FROM BARK OF MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl.) AND ITS ANTIOXIDANT ACTIVITY - Susilawati Susilawati; Sabirin Matsjeh; Harno Dwi Pranowo; Chairil Anwar (Universitas Gadjah Mada, 2012)
Mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl.) which is belong to family of Thymelaeaceae is one of Indonesian traditional medicines. Chemical constituent has been isolated from bark of mahkota dewa. Sample was extracted with methanol. Concentrated methanol extract was extracted by n-hexane, chloroform and ethyl acetate. A Compound that separated and purified by column chromatography from ethyl acetate extract is a red spherical crystal (m.p. 94-95 °C). Its spot gave yellow fluorescence at TLC plate (UV366) and has optical rotation of -9.3°(c. 2 mg/mL, methanol). Structure elucidation by UV, IR, 1H-NMR, 13C-NMR and NMR 2 dimension (HMQC, COSY, HMBC and DEPT-135) spectroscopy show that the compound gives a name macronone. Computational chemistry calculation using Hyperchem on the level of semiempirical method PM3 was confirmed the conformation of macronone. DPPH method shows that macronone has lower antioxidant activity compare to the ethyl acetate extract.